Morphology and phylogeny of two new species within Cordycipitaceae (Hypocreales) from China - Yingling Lu; Songyu Li; Zuoheng Liu; Jing Zhao; Zhiyong Yu; Zongli Liang; Hailong He; Jianhong Li; Yun Huang; Xinming Li; Hong Yu (MycoKeys)
Simplicillium and Leptobacillium, sister genera in the family Cordycipitaceae, exhibit a broad range of hosts or substrates. The identification of two novel species, from Simplicillium and Leptobacillium, was achieved by analysing morphological characteristics and phylogenetic data obtained from six molecular markers (ITS, nrSSU, nrLSU, tef-1α, rpb1 and rpb2). The two recently documented species are S. puwenense and L. longiphialidum. Morphologically, S. puwenense possessed slender solitary rod-shaped or columnar phialides with elliptical oval or cylindrical conidia forming small spherical heads at the apex of phialides. On the other hand, L. longiphialidum had solitary columnar phialides with elliptic or subspherical apical conidia while other conidia were narrow columnar or fusiform in shape. Phylogenetic analysis revealed that S. puwenense formed an independent branch as a sister species to S. formicae, whereas L. longiphialidum clustered with L. marksiae exhibiting stable topological structure. The Bayesian inference posterior probability and the maximum likelihood bootstrap-ratio provided robust statistical evidence, indicating the presence of two novel species within the genera of Simplicillium and Leptobacillium. The present study contributes to the discovery of species diversity in Simplicillium and Leptobacillium, while also providing a taxonomic foundation for their rational development and sustainable utilisation.